Annual Address to the Board of Governors, September 26, 1966 - Woods, George D. (World Bank, Washington, DC, 2019)
George D. Woods, President of the World Bank Group, points out the activities well established by the Bank in its 20th year. He discusses: 1) International Development Association financing of education and agriculture, which includes among other things fertilizer components and plants, highways, irrigation, and credit for small agriculturists; 2) two projects aimed at increasing the willingness of the private entrepreneur and investor to venture abroad; 3) problems that confront economic developments; and 4) some specific achievements.